FROM COUNTERBALANCING TO ENGAGING CHINA: SHIFT IN JAPAN’S APPROACH TOWARDS THE NEW INTERNATIONAL ORDER IN THE ASIA-PACIFIC UNDER THE SECOND ABE ADMINISTRATION - Żakowski, Karol (Torun International Studies, 2019)
Since returning to the post of prime minister in 2012, Abe Shinzō has been promoting Japan’s active posture in maintaining international stability in the Asia-Pacific. Abe’s vision of the new international order in the region has been based on Tokyo’s alliance with Washington, both in the security and economic spheres. Through legalization of Japan’s participation in collective self-defense pacts and revision of the Guidelines for Japan–US Defense Cooperation in 2015, Abe strengthened the Japan–US alliance. In parallel, he promoted Japan’s participation in the Trans-Pacific Partnership (TPP), which however was realized as Comprehensive and Progressive Agreement for Trans-Pacific Partnership without the Trump administration’s participation. In addition, Tokyo has been negotiating Regional Comprehensive Economic Partnership (RCEP), Japan–China–Republic of Korea Trilateral Free Trade Agreement, and Free Trade Area of the Asia-Pacific. The article argues that while initially the Japanese prime minister’s regional initiatives were aimed at counterbalancing China’s rise, they gradually started putting more emphasis on engaging China in international cooperation. Applying a neoclassical-realist methodology, this study examines both the international and the domestic determinants of Japan’s shift in approach towards the new international order.